The complex nature of constitutional de novo apparently balanced translocations in patients presenting with abnormal phenotypes. Issue 1 (5th January 2005) - Gribble, S M; Prigmore, E; Burford, D C; Porter, K M; Ng, Bee Ling; Douglas, E J; Fiegler, H; Carr, P; Kalaitzopoulos, D; Clegg, S; Sandstrom, R; Temple, I K; et al.
Abstract : Objective: To describe the systematic analysis of constitutional de novo apparently balanced translocations in patients presenting with abnormal phenotypes, characterise the structural chromosome rearrangements, map the translocation breakpoints, and report detectable genomic imbalances. Methods: DNA microarrays were used with a resolution of 1 Mb for the detailed genome-wide analysis of the patients. Array CGH was used to screen for genomic imbalance and array painting to map chromosome breakpoints rapidly. These two methods facilitate rapid analysis of translocation breakpoints and screening for cryptic chromosome imbalance. Breakpoints of rearrangements were further refined (to the level of spanning clones) using fluorescence in situ hybridisation where appropriate. Results: Unexpected additional complexity or genome imbalance was found in six of 10 patients studied. The patients could be grouped according to the general nature of the karyotype rearrangement as follows: (A) three cases with complex multiple rearrangements including deletions, inversions, and insertions at or near one or both breakpoints; (B) three cases in which, while the translocations appeared to be balanced, microarray analysis identified previously unrecognised imbalance on chromosomes unrelated to the translocation; (C) four cases in which the translocation breakpoints appeared simple and balanced at the resolution used. Conclusions: This high level of unexpected rearrangement complexity, if generally confirmed in the study of further patients, will have an impact on current diagnostic investigations of this type and provides an argument for the more widespread adoption of microarray analysis or other high resolution genome-wide screens for chromosome imbalance and rearrangement.